Withaferin A Suppresses Beta Amyloid in APP Expressing Cells: Studies for Tat and Cocaine Associated Neurological Dysfunctions - Tiwari, Sneham; Atluri, Venkata Subba Rao; Yndart Arias, Adriana; Jayant, Rahul Dev; Kaushik, Ajeet; Geiger, Jonathan; Nair, Madhavan N. (Frontiers in Aging Neuroscience, 2018)
Neurological disorders are the biggest concern globally. Out of 36 million human immunodeficiency virus (HIV) positive people, about 30%–60% exhibit neurological disorders, including dementia and Alzheimer’s disease (AD) like pathology. In AD or AD like neurological disorders, the pathogenesis is mainly due to the abnormal accumulation of extracellular amyloid beta (Aβ). In this era of antiretroviral therapy, the life span of the HIV-infected individuals has increased leading towards increased neurocognitive dysfunction in nearly 30% of HIV-infected individuals, specifically older people. Deposition of the Aβ plaques in the CNS is one the major phenomenon happening in aging HIV patients. ART suppresses the viral replication, but the neurotoxic protein (Tat) is still produced and results in increased levels of Aβ. Furthermore, drugs of abuse like cocaine (coc) is known to induce the HIV associated neurocognitive disorders as well as the Aβ secretion. To target the Tat and coc induced Aβ secretion, we propose a potent bifunctional molecule Withaferin A (WA) which may act as a neuro-protectant against Aβ neurotoxicity. In this study, we show that WA reduces secreted Aβ and induced neurotoxicity in amyloid precursor protein (APP)-plasmid transfected SH-SY5Y cells (SH-APP). In this study, we show that in SH-APP cells, Aβ secretion is induced in the presence of HIV-1 Tat (neurotoxic) and drug of abuse coc. Our fluorescent microscopy studies show the increased concentration of Aβ40 in Tat (50 ng/ml) and coc (0.1 μM) treated SH-APP cells as compared to control. Our dose optimization study show, lower concentrations (0.5–2 μM) of WA significantly reduce the Aβ40 levels, without inducing cytotoxicity in the SH-APP cells. Additionally, WA reduces the Tat and cocaine induced Aβ levels. Therefore, we propose that Aβ aggregation is induced by the presence of Tat and coc and WA is potent in reducing the secreted Aβ and induced neurotoxicity. Our study provides new opportunities for exploring the pathophysiology and targeting the neurological disorders.